Mapping heavy metals accumulation in conventional rice farming system at Banyumas Regency of Central Java, Indonesia - Yugi R Ahadiyat; Ahmad Fauzi; Okti Herliana; Sapto Nugroho Hadi (Journal of Degraded and Mining Lands Management, 2023)
Rice grains produced in the conventional system are a prime source of heavy metal exposure in the human body leading to various health problems. The objective of this study was to assess heavy metals concentration in soil and rice grain under the conventional rice farming system in Banyumas, Indonesia, the pollution index, and the bioaccumulation factor. There were thirty-seven samples collected based on soil type, elevation, and irrigation system. The heavy metals level in soil ranged from 2.7 to 39.92 ppm of Pb, 0.11 to 3.01 ppm of Cd, and 4.79 to 61.32 ppm of Cr. Pb and Cr accumulation levels were below the maximum permissible concentration (MPC). A different result in Cd exceeded the MPC in 56.75% of sampling sites. Rice grain showed a high accumulation in Pb (6.85 ppm) and Cr (5.73 ppm) that exceeds the maximum standard. Cd exceeded 24.32% of sampling sites with an average of 0.54 ppm. The Pollution Index (PI) was medium in Cd and low in Pb and Cr. The Bioaccumulation Factor (BAF) of heavy metals in rice was Cd>Pb>Cr with averages of 0.64, 0.53, and 0.30, respectively. A high correlation resulted in Pb and Cd in soils and rice grains. Remediation is must done to reduce the heavy metals accumulation in soils and rice grains for environmental and health safety to prevent further contamination.